HUBUNGAN DUKUNGAN KELUARGA DAN PETUGAS KESEHATAN DENGAN KEPATUHAN MINUM OBAT PADA PASIEN TB PARU DI WILAYAH KERJA PUSKESMAS TELAGA - Pipin Yunus; Abdul Wahab Pakaya; Belawati Hadju (Journal of Educational Innovation and Public Health, 2023)
Pulmonary tuberculosis is an infectious disease that can be prevented and cured, but takes a long time so whether treatment is successful or not is influenced by the support of families and health workers. The purpose of this research was to determine the relationship between family support and health workers with medication adherence in pulmonary TB patients. This study used quantitative methods with a cross-sectional approach, Sampling using accidental sampling technique with a total sample of 34 people.. Data collection using questionnaire sheets and data analysis using univariate and bivariate analysis with chi-square test. The results of the study obtained good family support for the majority of compliance by 52.94% and poor family support by the majority of non-compliance by 29.4%, as well as the support of health workers in the majority of compliance by 59.94% and no support of health workers in the majority of non-compliance by 23.53%, the results of the chi-square statistical test obtained there was a relationship of family support (p-value=0.000) and health worker support (p-value= 0.004) with adherence to taking medications. It can be concluded that pulmonary TB patients who receive support from family and health workers can affect the patient's compliance in taking medications.